Failure analysis and optimization of a suspended structure in the power supply system of the subway. (September 2020) - Liu, Long; Ding, Ning; Xu, Na; Guo, Weimin; Shi, Junbo; Li, Nan; Zhang, Lijun; Meng, Bingchen; Zaïri, Fahmi
Highlights: The fractured droppers due to fatigue crack propagation were analyzed. The initial region was located at a notch near the bending place of droppers. The residual strength will increase as the increasing of the chamfering radius. Improvement the manufacturing tool was an effective way to improve the service life. Abstract: The failure mechanism of the fractured droppers used in power supply systems for subway was analyzed with various technologies. Collected evidences indicated that the droppers fracture due to fatigue crack propagation. The chemical composition and mechanical properties of the dropper material were both complied with the normal 304 stainless steel standard. The metallographic examination showed that the microstructure of the failed dropper was normal. The initial region of the fatigue damage was located at a notch near the bending place. Under the cyclic loads caused by the up and downs of the dropper when the train passes by, the crack initiated, propagated and ruptured finally. Results of finite element simulations suggested that the residual force of the droppers will increase as the chamfering radius is. Improving the manufacturing tool was an effective way to reduce the stress concentration and to increase the residual force of the droppers, thus, to improve the service life of the droppers.